Hubungan Peran Serta Orang Tua dan Dampak Hospitalisasi pada Anak Prasekolah - Tini Inggriani; Deni Budiani Permana (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2021)
Hospitalization of children, either directly or indirectly affects their psychological aspects. It even creates a crisis. Parents as close figures have an important role to accompany and provide encouragement so that they can minimize the impact of hospitalization. The study was conducted to determine the relationship between parental participation and the impact of hospitalization of children who were treated at the hospital. Lebak Mission. The study was designed as a correlational study with a cross sectional approach. The research sample was 53 children. The instrument is a questionnaire. Data were analyzed by Chi-Square test and Mann-Whitney test. There is a significant relationship between the role of parents and the impact of hospitalization on children at the Lebak Mission Hospital, as shown from the Chi-Square test results obtained p-value = 0.000 which is smaller than 0.05. Partially there is a significant relationship between the characteristics of children and the characteristics of parents with the impact of hospitalization, as indicated by the p-value which is smaller than 0.05. Meanwhile, the characteristics of age and parental education do not have a relationship, because the p-value is greater than 0.05. There is a significant relationship between parental participation and the impact of hospitalization on children at the Lebak Mission Hospital. the need for better nurse involvement so that the negative impact of hospitalization on children can be minimized.